Sistem Informasi Absensi, Penggajian, dan Pinjaman Pegawai pada PT. X - Annisa Paramitha F; Ramdani Febrianto (Jurnal Manajemen Informatika (JAMIKA), 2020)
PT. X is a manufacturing company, which makes production machines and supporting parts. PT X does not yet fully have an information sistemfor company administration processes, therefore some obstacles occur because the company has not implemented a computer-based information sistem(CBIS). The company has problems with attendance, payroll, and employee loan processes. The company is currently still using Microsoft Excel as a tool for employee administration activities. The use of MS. Excel is quite helpful, but there are still deficiencies in the process of recording data and reporting. Therefore, it is necessary to design a sistemthat is connected to the database so that administrative activities can be well integrated and avoid data redundancy. In this study, the system development method used is the prototype method, while the sistems approach method used is Object-Oriented with analysis and design tools using UML. The results of this study are in the form of attendance information sistemdesign, payroll, and employee loans.